Evaluation of Knee Position Sense in Children with Motor Disabilities and Children with Typical Development: A Cross-Sectional Study - Åsa Bartonek; Marie Eriksson; Annika Ericson; Mikael Reimeringer; Cecilia Lidbeck (Children, 2023)
Background: In children with motor disabilities, knee position during walking is often of concern in rehabilitation. This study aimed to investigate knee joint position sense. Thirty-seven children with Cerebral Palsy (CP), 21 with Myelomeningocele (MMC), 19 with Arthrogryposis (AMC), and 42 TD children participated in the study. Knee joint position sense, i.e., the difference between the criterion angle and the reproduced angle (JPS-error), was assessed in sitting while 3D motion capture was recorded at flexed knee 70 (Knee70), 45 (Knee45), and 20 (Knee20) degrees, and after three seconds at maintained criterion angle (CAM) and maintained reproduced angle (RAM). No differences were found between the groups in JPS-error, CAM, and RAM. At Knee70, CAM differed between the right and left legs in the TD group (p = 0.014) and RAM in the MMC group (p = 0.021). In the CP group, CAM was greater than RAM at Knee70 in the left leg (p = 0.002), at Knee45 in both legs (p = 0.004, p = 0.025), and at Knee20 in the right leg (p = 0.038). Difficulties in maintaining the knee position at CAM in the CP group sheds light on the need for complementary judgments of limb proprioception in space to explore the potential influence on knee position during walking.